Breed Selection of Poplars Imposes Greater Selection Pressure on the Rhizosphere Bacterial Community - Jinliang Liu; Long Zhou; Yan Lan; Junfeng Fan (Microorganisms)
Breed selection alters the coevolution of plant–microbiome associations that have developed over long periods of natural evolution. We investigated the effects of breed selection on the rhizosphere microbiomes and metabolites of hybrid parents (I101 and 84K) and their offspring (Q1–Q5) using metagenomics and untargeted metabolomics. Rhizosphere archaeal, bacterial and fungal community β-diversity significantly differed among hybrid parents and offspring, but only the dominant bacterial phyla and bacterial community α-diversity revealed significant differences. Approximately 5.49%, 14.90% and 7.86% of the archaeal, bacterial and fungal species significantly differed among the poplar hybrid parents and offspring. Rhizosphere microbial functional genes and metabolites were both clustered into the following three groups: I101 and 84K; Q2 and Q4; and Q1, Q3 and Q5. Compared with the hybrid parents, 15 phytochemical compounds were enriched in the hybrid offspring and explained 7.15%, 18.24% and 6.68% of the total variation in the archaeal, bacterial and fungal community compositions, respectively. Rhizosphere metabolites significantly affected the bacterial community, rather than the archaeal and fungal communities. Our observations suggested that poplar breed selection imposed greater selection pressure on the rhizosphere bacterial community, which was mainly driven by metabolites.